Evidence that genetic variation in 5-HT transporter expression is linked to changes in 5-HT2A receptor function. - Jennings, K; Sheward, W; Harmar, A; Sharp, T (2008)
Variability in expression of the 5-HT transporter (5-HTT) gene in the human population has been associated with a range of behavioural phenotypes. The underlying mechanisms are unclear but may involve changes in 5-HT receptor levels and/or signalling. The present study used a novel 5-HTT overexpressing transgenic mouse to test the hypothesis that variability in 5-HTT expression may alter 5-HT(2A) receptor function. In wildtype mice, the 5-HT(2) receptor agonist DOI increased regional brain mRNA expression of two immediate early genes (c-fos and Arc), and induced head twitches, and both effects were abolished by pre-treatment with the 5-HT(2A) receptor antagonist MDL 100907. In 5-HTT overexpressing mice, DOI induced a greater increase in both c-fos and Arc mRNA expression in cortical brain regions, and more head twitches, compared to wildtype mice. Autoradiographic and in situ hybridisation experiments showed that 5-HT(2A) receptor binding sites and 5-HT(2A) receptor mRNA did not differ between transgenic and wildtype mice. Finally, the transgenic mice had lower regional brain 5-HT levels compared to wildtype mice. This depletion of 5-HT may underpin the increase in 5-HT(2A) receptor function because in wildtype mice 5-HT depletion using the 5-HT synthesis inhibitor, p-chlorophenylalanine, enhanced the head twitch response to DOI. These data demonstrate that elevated 5-HTT expression is accompanied by increased 5-HT(2A) receptor function, an effect possibly mediated by decreased availability of synaptic 5-HT. Variation in levels of 5-HTT expression may therefore be a source of variability in 5-HT(2A) receptor function, which may be an important modifier of 5-HTT-linked phenotypes.